A study on non-communicable diseases, it’s prevalence on anthropometric and behavioural risk factors on tribal population of Raigad district: a cross sectional study - Parle, Jyoti Ajit; Yadav, Manali N.; Raut, Kishor (International Journal Of Community Medicine And Public Health, 2021)
Background: Non-communicable diseases (NCDs) are increasing at an alarming rate due to lifestyle modifications and increased level of stress but the prevalence of it in tribal population is still lacking. Thus, the study aimed at identifying the risk factors for non-communicable diseases among healthy adults aged 16-80 years in the tribal population of Raigad district. Methods: A cross-sectional survey was done with 920 individuals aged 16-80 years of tribal population. Each subject was interviewed using the WHO stepwise questionnaire; where information on diet, physical activity, tobacco and alcohol, and treatment history for hypertension and diabetes were collected along with blood pressure (BP) measurement. Height, weight and waist circumference were also measured. Results: Statistical analysis was done using SPSS version 24. Moderate prevalence of smoking and smokeless tobacco was observed in the tribal areas targeted with the number of smokers being more than the users of smokeless tobacco. Consumption of alcohol was seen in half of the population in the age group of 16-50 years. Low consumption of fruits and vegetables was seen across all the age groups. Most of the target population falls under the normal BMI category while a fewer population falls under the overweight category. Conclusions: High prevalence of behavioural risk factors were found with awareness about NCD’s was found to be alarmingly low among the tribal population. Prevention of NCD’s through detection of risk factor can control the spread of non-communicable diseases, and will help in identifying earlier with its detection and treatment same as communicable diseases.